Большая книга игр: более 1500 веселых, полезных и интересных игр / [художник С. Киселева] - Киселева Светлана (Эксмо, 2007)
Экземпляры: ДБ/6/13/14/15 (20250129) / Инвентарный номер: 43511 / Цена: 144.30 / Сис.шифр: 74.100.58 / Авт.знак: Б 79 / ГРНТИ: 14 / ББК: 74.100.58